Welchen Beitrag leistet die peer group für die Lesemotivation von Schülerinnen und Schülern zu Beginn der Sekundarstufe? - Gölitz, Dietmar; et al. (Psychologie in Erziehung und Unterricht, 2010)
Interest in the acquisition of reading literacy and reading motivation by means of schooling and extracurricular activities has grown in the years since the publication of the PISA 2000 study. Whereas the role of the family in reading socialization is well established, little is known about the influence of children's same-age friends on their motivation to read. Therefore, a sample of N = 501 children who were ten to eleven years old and attended fifth grade in three different school tracks (Hauptschule, Realschule, Gymnasium) was asked by means of a questionnaire. A structural equation model showed that participants' perceptions of their peer group's attitude towards reading contributed to explaining their reading motivation besides gender and reading related self-perceptions..
Keywords: 3 Förderung Kognition; Deutschdidaktik; Koblenz; Lesen; Peers; Mediennutzung